Characterization of the chloroplast genome of the Osmanthus didymopetalus. Issue 3 (2nd July 2020) - Zhao, Changheng; Yang, Qinghua; Zhang, Min; Zhang, Cheng; Wang, Xiaofei; Wang, Xianrong; Li, Yongfu
Abstract: In this study, we assembled the chloroplast genome of Osmanthus didymopetalus (Oleaceae), a rare evergreen tree native to Hainan, China. The genome of O. didymopetalus was 155, 155 bp in length and contained a pair of inverted repeats (IR, 25, 697–25, 704 bp) regions, which were separated by the small single copy (SSC, 17, 591 bp) and the large single copy (LSC, 86, 225 bp) regions. The cp genome encoded 133 genes including 88 protein-coding genes, 37 tRNA genes, and eight rRNA ribosomal genes. The overall GC content of O. didymopetalus chloroplast genome is 37.8%. Phylogenetic results showed that O. didymopetalus was more closely to O. yunnanensis, O. fragrans and O. insulari s. This study will be beneficial for the evolutionary study and phylogenetic reconstruction of Osmanthus .